The use of camera-traps in a survey of the buff-headed capuchin monkey, Cebus xanthosternos - Kierulff, Maria Cecília Martins; Santos, Gabriel Rodrigues; Canale, Gustavo; Guidorizzi, Carlos Eduardo; Cassano, Camila (Neotropical Primates, 2004)
No abstract